2014
DOI: 10.1080/13607863.2014.967171
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of social support in older American Indians: the Native Elder Care Study

Abstract: Objectives This study examined social support and identified demographic and health correlates among American Indians aged 55 years and older. Methods Data were derived from the Native Elder Care Study, a cross-sectional study of 505 community-dwelling American Indians aged ≥55 years. Social support was assessed using the Medical Outcomes Study Social Support Survey measure (MOS-SSS) of which psychometric properties were examined through factor analyses. Logistic regression analyses were used to identify ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Living on tribal lands or a reservation compared to an urban setting may have important implications in the prevalence of psychological trauma exposure and social support. Future research needs to examine these associations among American Indian men as mental health prevalence and conditions differs by sex (Beals, Novins, et al, 2005; Brave Heart et al, 2016) as does social support (Conte, Schure, & Goins, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Living on tribal lands or a reservation compared to an urban setting may have important implications in the prevalence of psychological trauma exposure and social support. Future research needs to examine these associations among American Indian men as mental health prevalence and conditions differs by sex (Beals, Novins, et al, 2005; Brave Heart et al, 2016) as does social support (Conte, Schure, & Goins, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon also substantiated that the marriage is an important source of social support. Married patients had higher social support 39 41. Additionally, the factor of household size among the patients was a significant determinant of social support.…”
Section: Discussionmentioning
confidence: 90%
“…The findings of the study are consistent with a study conducted among Indians in America. They revealed that the respect for elders is an important traditional value that may translate into higher social support in American Indians 39…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a complex experience that is characterised as the interrelationship between biological, psychological, and sociocultural aspects, and the experience and expression of pain may be culturally influenced. In a study of social support among older American indigenous peoples, Conte et al found that less persistent pain was linked to higher social support, and that increased age, being married, and being female were factors associated with high social support [50]. In the Sami culture, closeness to relatives and the presence of an extended family is important, especially among elderly Sami women [51].…”
Section: Discussionmentioning
confidence: 99%